Andrographolide Protects against LPS-Induced Acute Lung Injury by Inactivation of NF-κB - Zhu, Tao; Wang, Dao-xin; Zhang, Wei; Liao, Xiu-qing; Guan, Xian; Bo, Hong; Sun, Jia-yang; Huang, Ni-wen; He, Jing; Zhang, Yun-kun; Tong, Jing; Li, Chang-yi (PloS one, 2013)
Nuclear factor-κB (NF-κB) is a central transcriptional factor and a pleiotropic regulator of many genes involved in acute lung injury. Andrographolide is found in the plant of Andrographis paniculata and widely used in Traditional Chinese Medicine, exhibiting potently anti-inflammatory property by inhibiting NF-κB activity. The purpose of our investigation was designed to reveal the effect of andrographolide on various aspects of LPS induced inflammation in vivo and in vitro. In vivo, BALB/C mice were subjected to LPS injection with or without andrographolide treatments to induce ALI model. In vitro, MLE-12 cells were stimulated with LPS in the presence and absence of andrographolide. In vivo, pulmonary inflammation, pulmonary edema, ultrastructure changes of type II alveolar epithelial cells, MPO activity, total cells, neutrophils, macrophages, TNF-α, IL-6 and IL-1β in BALF, along with the expression of VCAM-1 and VEGF were dose-dependently attenuated by andrographolide. Meanwhile, in vitro, the expression of VCAM-1 and VEGF was also reduced by andrographolide. Moreover, our data showed that andrographolide significantly inhibited the ratios of phospho-IKKβ/total IKKβ, phospho-IκBα/total IκBα and phospho-NF-κB p65/total NF-κB p65, and NF-κB p65 DNA binding activities, both in vivo and in vitro. These results indicate that andrographolide dose-dependently suppressed the severity of LPS-induced ALI, more likely by virtue of andrographolide-mediated NF-κB inhibition at the level of IKKβ activation. These results suggest andrographolide may be considered as an effective and safe drug for the potential treatment of ALI.